2021
DOI: 10.9734/jpri/2021/v33i1531283
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Sirtuin 1 by Ellagic Acid Ameliorates Cisplatin-Induced Apoptosis, Oxidative Stress and Nephrotoxicity

Abstract: Background: Cisplatin (Cis) is a chemotherapeutic agent commonly applied in treating different cancers. However, acute renal injury remains a major side effect of Cis that limits its clinical use. Oxidative stress in renal tissues play a key role in Cis-induced toxicity. This research aimed to investigate the impact of ellagic acid (Ella) on Cis-induced apoptotic renal injury and the possible involvement of sirtuin 1 (SIRT1) and oxidative stress as a possible protective mechanism. Methods: Twenty-four Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Here, we showed that EA administration ameliorated age-associated renal dysfunction and histopathological alterations, which is thought to be mediated through SIRT1. Similar findings of improved renal function and histopathological features mediated by SIRT1 were also reported in several rat models of nephrotoxicity [17,28].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Here, we showed that EA administration ameliorated age-associated renal dysfunction and histopathological alterations, which is thought to be mediated through SIRT1. Similar findings of improved renal function and histopathological features mediated by SIRT1 were also reported in several rat models of nephrotoxicity [17,28].…”
Section: Discussionsupporting
confidence: 85%
“…EA, a natural polyphenolic compound, has received considerable attention because of its various biological properties, such as radical scavenging, anti-inflammatory, antiviral, cancer, and diabetes-prevention activities [14]. A recent study reported that EA administration significantly enhanced the expression of SIRT1 in rat kidneys and ameliorated cisplatin-induced nephrotoxicity [28]. Additionally, EA has been shown to protect renal tissues against iron oxide-induced damage by promoting the expression of SIRT1 [17].…”
Section: Discussionmentioning
confidence: 99%